Influencia de las redes sociales en el incorrecto uso de las normas ortográficas en estudiantes de 18 – 23 años de la Universidad Nacional de Chimborazo, periodo julio – diciembre 2022 - Piáun Chalcualán, Cinthya Pamela (2024)
ABSTRACT: This research deals with the influence of social networks on the writing skills of students aged 18-23 years, July- December 2022. Social networks offer us various services and functions, to achieve better communication within the virtual space, however, spelling errors are noted in their publications, but, above all, new forms of communication are being created, turning it into a cyber language. The sustentation of the research was complemented in the theoretical framework using basic concepts such as communication, language, paradigmatic linguistic theory, types of social networks, semiotics, and morphology, among other topics. This will help us to deepen how new forms of communication have been gaining strength over time, i.e., the transformation of the language used within social networks. To obtain results, a quantitative and qualitative methodology was applied, including surveys, interviews, and a content analysis matrix that will help determine the causes of the problem within these cyberspaces. The main conclusion is that cyberspaces allow us to communicate and interact with others, however, it has also allowed us to transform the language into a more understandable one, for example: omitting words, using emoticons, among others, alluding to modern language. The purpose of this article is for you to know the importance of making correct use of spelling rules in social networks.